Kajian Visual Gambar Beber Karya Soegeng Toekio Tahun 2011-2012 - Chaidir, Muhammad (Brikolase : Jurnal Kajian Teori, Praktik dan Wacana Seni Budaya Rupa, 2013)
This thesis examines the visual images beber from Soegeng Tekio 's art work in 2011-2012. Soegeng Toekio began a cultural approach to explore the myths, legends, folklore and also a source of other lexis, including the history and ritual activities as well as a theme in his work concept. This type of research is descriptive qualitative study using a theoretical approach Monroe Beardsley. Based on the elements of art, we can conclude that Soegeng Toekio has managed to cultivate such a wayang beber beber image into the form of work that characterizes his work. For example Soegeng Toekio using comics in the shape of the face as he explained the picture, but the shape of posture using realistic proportions. In addition Soegeng Toekio also has a strong character lines in sunggingnya concept and the theme of his work is always related to cultural traditions that exist in Indonesia archipelago.Â Keywords; beber image, the process was working, meaning.